Sistem Pemasaran Kopi Bubuk Sari Buana pada UD. Mega Jaya - PURNAMA , IDA BAGUS OKA; PARINING , NYOMAN; SARJANA , I DEWA GD. RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol. 1, No. 1, Juli 2012, 2012)
ABSTRACT Marketing System of Sari Buana Coffee Powder at UD. Mega Jaya Ground coffee is a beverage that is very common and widespread in the surrounding communities. The success of the company to deliver products to consumers will require a merchant supplier, in the form of marketing agencies to quickly get to the consumer product. The role of the marketing agency is required by companies to market their products. This study aims to determine: 1) the marketing of coffee powder Sari Buana marketing at UD. Mega Jaya. 2) the magnitude of marketing margins in each of the agencies involved in each marketing channel. The research was conducted at UD. Mega Jaya, Central Singapadu Village, District Sukawati, Gianyar Regency. Data obtained from the field were analyzed with descriptive methods and analysis of marketing margins. The study found that the marketing of coffee powder in UD. Mega Buana Sari Jaya starts from the manufacturers, marketing agencies, and distribution. UD. Mega Jaya is a producer Sari Buana ground coffee that has multiple functions in the conduct of marketing such products, has a raw material procurement, production, product inventory, production costs, choose a marketing agency, pricing, promotion, delivery, ordering, and well received by the company's risk. Marketing agencies involved in marketing products in the company starting from major retailers and small retailers that distribute products to end customers. So that products marketed to consumers quickly end. Marketing channel consists of four channels, namely: 1) Company - Large - Small Retailer - Consumer. 2) Company - Large Retailer - Consumer. 3) Company - Small Retailer - Consumer. 4) Company - Consumer. Of the channel obtained the highest sales volume at the company's channel I and III. Marketing margins in the channel I is equal Rp.2.500 (5.882%), channel II Rp. 2500 (5882%), channel III Rp. 1000 (2.352%) and Rp IV line. 0 (0%). Judging from the company's product sales volume, the first marketing channel is the channel of the most highest level of sales as compared to other channels. So it is recommended to do further research to determine the most effective channels and profitable for the company and UD. Mega Jaya should be much more to maximize the performance of existing marketing channels by controlling the marketing of all existing institutions. Key words: marketing, coffee powder, marketing margins